THE DEFENSE ACTIVITY AS VULNERABILIS COSTS IN COLLECTIVE ACTIONS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The protection of excluded, invisible and vulnerable groups, this is the public role of the Public Defender's Office in collective actions. The objective is to clarify that the Public Defender's Office was created for the defense of the needy in a broad sense, and not limited to the underprivileged in the strictly economic sense. This is confirmed by the constitutional change made by constitutional amendment number 80/2004, as well as by the need to make the primacy of access to justice and the strengthening of human rights more effective. In the text, the work of the Public Defender's Office focuses on vulnerability costs in three circumstances, in criminal execution, in possessory matters and in favor of the quilombola community. For that, bibliographic research was used as the procedure method and the bibliographic deductive approach method. Finally, the approach perspective is qualitative, since it involves descriptive information.